Effectiveness of Bonding Steel Elements with Polyester-Coated Paint - Anna Rudawska; Arkadiusz Gola; Jakub Pizoń; Paweł Capała; Łukasz Wójcik (Applied Sciences, 2023)
The aim of the paper is to assess the impact of the effectiveness of bonding steel elements with paint coating. The adhesive joints were made using two types of the adhesives: two-component epoxy resin adhesive based on Bisphenol A and polyurethane. Three types of adhesive joints were made: (i) reference samples, (ii) samples with a paint polyester coating, and (iii) samples with a zinc primer and paint polyester coating. These coatings were applied using the electrokinetic method. A shear strength test of the adhesive joints (EN DIN 1465 standard), a coating adhesion test (ASTM D3359-B standard), and surface wettability tests (based on contact angle) were used. Through analyzing the test results, it can be seen that the strength of the adhesive joints of the reference samples made with epoxy adhesive is 46% lower than that of the specimens with primer and paint coating applied. However, in the case of the adhesive joints made with the polyurethane adhesive, the aforementioned difference in the strength value of the adhesive joints of the reference samples and paint-coated samples with an applied primer is 76%. Adherends with a paint coating and a previously applied primer obtained the lowest value of the contact angle (38.72°) and are characterized by good wettability.